Implementation of Discipline-Based Character Education Management Through Teacher-Parent Collaboration at Babussalam Junior High School in East Lombok - Ariani, Silvia; Jakandar, Lalu Iwan Eko; Fikriah, Asfa (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2026)
This study examines the practice of collaborative discipline-based character education management between teachers and parents at Babussalam Junior High School in East Lombok, an Islamic school located in a unique socio-religious context. This study stems from the need to understand how school and family collaboration is managed in fostering student discipline, particularly in Islamic schools located in non-urban areas. The research uses a qualitative approach with a case study design. Data were obtained through in-depth interviews, participatory observation, and documentation studies, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results show that character discipline development is managed through stages of planning, implementation, and evaluation involving school actors and parents in daily managerial practices. Collaboration is realized through various forms of communication, monitoring of student behavior, and parental involvement in the character evaluation process. The research findings also reveal obstacles in the implementation of collaboration, including variations in parental participation, differences in disciplinary habits at home, and technical and administrative limitations of the school. To respond to these conditions, schools implement flexible and contextual managerial adaptation strategies. This study confirms that the management of character education in Islamic schools requires a collaborative approach that is adaptive to the dynamics of the relationship between schools and families. These findings provide empirical contributions to the study of Islamic education management, particularly in understanding teacher-parent collaboration practices in character building at the junior high school level.